Free Movement of Goods and the Right to Protest : Examining how the European Court of Justice Finds a Balance Between Free Movement of Goods and the Rights to Freedom of Expression and Assembly - Juntunen, Aino (My University, 2025)
This paper examines how the European Court of Justice adjudicates cases where the right to protest, made up of the right to freedom of expression and the right to assembly, come into conflict with the fundamental freedom of free movement of goods. Specifically, the paper will try to answer the question “what are the key points of consideration in cases where the right to protest comes in odds with free movement of goods?”. A central part of this analysis will come from studying the CJEU judgements Schmidberger and Commission v. France. This analysis is supplemented with the work of many scholars of the field, including Stephanie Reynold’s article Explaining the Constitutional Drivers behind a Perceived Judicial Preference for Free Movement over Fundamental Rights, and the article Fundamental Rights and the Framework of Internal Market Adjudication: Is the Charter Making a Difference? by Niamh Nic Shuibhne. Lack of case law limits what conclusions can be drawn on this topic, but it can be said that the Court seems to overall apply a fundamental rights-oriented approach to cases concerning the right to protest. The Court’s argumentation does contain some problems, as it’s not always logical why it chooses to emphasize certain facts when determining how serious of a breach a demonstration causes. There is also some proof that the Court is generally more sympathetic to protesters with non-discriminatory, generally accepted aims like environmental concerns who do everything by the book, compared to protesters with discriminatory motives who conduct themselves in a more disorderly way.
Keywords: Free movement of goods, Fundamental Rights, Freedom of Expression, Freedom of Assembly